PLANT MEDIATED SYNTHESIS OF SILVER NANOPARTICLES BY USING DRIED STEM POWDER OF TINOSPORA CORDIFOLIA, ITS ANTIBACTERIAL ACTIVITY AND COMPARISON WITH ANTIBIOTICS - SAMIR A. ANUJ; KALPESH B. ISHNAVA (International Journal of Pharma and Bio Sciences, 2013)
It is a well-known fact that silver nanoparticles are highly toxic to microorganisms. So, nowadays the synthesis and antimicrobial activity of silver nanoparticles is a major area of research in the field of nanobiotechnology. The problem with most of the chemical and physical methods of silver nanoparticles is that they are expensive and can also involve the use of toxic, hazardous chemicals, which may pose biological and environmental risks. To overcome this, the biological method provides a feasible alternative. But a major drawback of using bacteria, algae and fungi to synthesize silver nanoparticles is that it is very slow and the cell culture maintaining process when in comparison with plant extracts. Hence, the use of plant materials to synthesize silver nanoparticles becomes an option that is feasible. The Tinospora cordifolia is an important medicinal plant. Recently, this plant also used in the synthesis of silver nanoparticles. In this present study, we have synthesized silver nanoparticles using Tinospora cordifolia dried stem powder from 1mM aqueous silver nitrate. Utilizing the reduced property of stem powder, silver nanoparticles were synthesized at room temperature. The stem powder extracts mixed with silver nitrate showed a gradual change in the color of the extracts from yellow to dark brown. The formation of silver nanoparticles was confirmed by UV-Visible spectrophotometer, X-Ray diffraction (XRD), Fourier transform infrared (FTIR), Energy dispersive spectroscopy (EDAX) and Transmission electron microscopy (TEM). The antibacterial activity of silver nanoparticles against antibiotic resistant bacteria is very important characteristic of silver nanoparticles. When we compare the silver nanoparticles with the antibiotics, it provides an idea about the efficiency of silver nanoparticles.